Каліксарен біс-гідроксиметилфосфонова кислота змінює механокінетичні параметри скорочення кільцевих гладеньких м’язів caecum щура, що викликані ацетилхоліном - Цимбалюк, О.В.; Онуфрийчук, О.В.; Мірошниченко, М.С.; Черенок, С.О.; Кальченко, В.І.; Костерін, С.О. (Видавничий дім "Академперіодика" НАН України, 2007)
We studied the inﬂuence of calixarene bis-hydroxymethylphosphone acid (code C99) on the mechanokinetic parameters of the acetylcholine-evoked contractions of smooth muscles caecum strips of rats. It is established that this substance inhibits the amplitude and selectively modiﬁes the mechanokinetic characteristics of contractions. The kinetic analysis has shown that the normalized maximal rate of contraction was not changed relative to control, and the normalized maximal rate of relaxation was signiﬁcantly inhibited by calixarene С99 in such a manner that the form of dependence of this parameter on the effector concentration changed from sigmoid (in control) to linear.